Predicting the adoption of “Buku Kedai”: a digital book-keeping application among Malaysian micro-entrepreneurs - Wan Noraswaniaty Wan Ahmad; Rabaatul Azira Hassan; Maheran Zakaria; Saifful Nazri Md Nazir; Dwi Suhartini (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2024)
The emergence of digital economies has led to the diffusion of digital innovation in business activities. A book-keeping digital application known as “Buku Kedai” is among the innovations invented by researchers to optimise entrepreneurial business performance. Despite offering tremendous benefits, its adoption is low. The intriguing phenomenon triggers the researchers to study the factors accelerating its adoption. Emulating the factors proposed by the theory of acceptance model (TAM), the researchers predict that adopting “Buku Kedai” is related to perceived usefulness, perceived ease of use and subjective norms. The researchers distributed 300 questionnaires to Malaysian micro-entrepreneurs. However, only 248 data proceeded for further analysis. Employing SPSS 27 and partial least square-structural equation model (PLS-SEM) 3, the results indicated that all three variables, namely perceived usefulness, perceived ease of use and subjective norms, are significant predictors of “Buku Kedai” adoption. The discoveries shed insights for policymakers, governments, and academia to formulate development programs for empowering entrepreneurs through digital and capability upscaling. Besides, the programs should encourage the involvement of social contacts to support microentrepreneurs in adopting “Buku Kedai”. Adopting the “Buku Kedai” application is crucial in enhancing microentrepreneurs' quality, viability, resilience, and competitiveness in pursuing success and sustainability.